IMPULSIVE ONLINE BUYING OF “Y” GENERATIONS - Setya, Yanto Azie; Juniarti, Anita Dyah (Management Science Research Journal, 2024)
The purpose of this study was to examine the effect of the Intensity of using Instagram, and Positive shopping emotion on Impulsive buying online on Y generations of Instagram social media users. Data analysis was performed on 150 respondents' from Y generation as buyers of convenience and shopping goods. Data analysis using regression with smartPLS software version 3.3.2 which was used to test the three hypotheses in this study. The results of data analysis show that the effect of the intensity of using Instagram to impulsive buying online and positive shopping emotion, and positive shopping emotion to impulsive buying online are significant among Y generation.